Electrochemical performance of plant trace element incorporated silver nanoparticles synthesis from Datura metel L. - Karuppiah Chinniah; Karthik Kannan; Vivek Maik; Vladimir Potemkin; Maria Grishina; Samuel Johnson Christopher Jeyaseelan; Arumugam Muthuvel; David Gnanasangeetha; Krishnamoorthy Gurushankar (Indonesian Journal of Biotechnology, 2023)
In our report, silver nanoparticles (AgNPs) were prepared from the leaf extract of Datura metel L. via the green synthesis method. Datura metel L. is a herbal medicinal plant from the Solanaceae family. The as‐prepared AgNPs were characterized using UV‐Vis spectrometer, X‐ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscopy (SEM) with Energy Dispersive X‐ray (EDAX) analysis. The peak appearance of a Surface Plasmon Resonance (SPR) at 415 nm suggested the creation of AgNPs in the UV‐Vis spectrum. The XRD pattern showed the face‐centered cubic crystal structure of AgNPs with organometallic complex phase. Based on the FTIR spectrum, the peaks revealed the existence of biomolecules. SEM images showed the shape of the clastic rocks and the EDAX profile authenticated the presence of Ag and plant trace element. The cyclic voltammetry, Chronopotentiometry, and electrochemical impedance spectroscopy analysis were performed on an as‐prepared Ag electrode. A specific capacitance of 267.59 F/g at 0.5 A/g and a cyclic retention of 83.7% after 5000 charge‐discharge cycles were obtained. Hence, this material could be utilized in supercapacitor energy storage devices.